Environmental assessment of solar thermal systems for the industrial sector. (1st March 2018) - Kylili, Angeliki; Fokaides, Paris A.; Ioannides, Andreas; Kalogirou, Soteris
Abstract: In Europe, about a third of the total final energy demand of the industrial sector is used for the generation of low temperature heat below 100 °C which could be satisfied by commercially available solar thermal applications. Although the technological readiness level of solar thermal technologies is currently in high levels, the recent energy mix data of industrial countries with high solar irradiation levels reveal that this potential still remains untapped. The key objective of this work is to quantify this unexploited potential and assess the environmental impact of industrial solar thermal systems (ISTS). Under this context, cradle-to-use Life Cycle Assessment (LCA) was conducted for the definition of the environmental performance of ISTS. A parametric analysis for the application of ISTS at selected European sites with diverse solar potential was also implemented to investigate the impact of solar potential on the life cycle performance of the systems. Taking into consideration the findings on the potential of carbon savings from the application of ISTS and in relevance to the European Union Emissions Trading System (EU ETS), scenarios of ISTS penetration and monetization into the industrial sector have also been developed. The findings of this work can be used by policy-makers as guidelines for the development of national strategic plans and financial incentives for the promotion of large-scale industrial solar thermal applications. The implementation of a parametric assessment on the environmental performance of ISTS for specific European geographical locations of diverse solar potential enabled the development of a 'Life Cycle Produced to Consumed Energy' Ratio, which indicated that applications located at lower latitudes (in the northern hemisphere) can achieve greater life cycle energy and carbon savings than ISTS applications found higher in latitude. In particular, large-scale ISTS applications were found to achieve energy and carbon savings ranging from 35 to 75 GJ and 2–5 tonnes of CO2 per kWth, depending on the geographical location. Highlights: Environmental impact assessment of industrial solar thermal systems (ISTS). LCIA results relate linearly to the nominal thermal power of the ISTSs. Carbon savings range from 35 to 75 GJ and 2–5 tonnes of CO2 per kWth of ISTS. Life Cycle Produced to Consumed Energy Ratio: 0.015 (37° lat.) ― 0.006 (60° lat.). Transportation environmental impact of ISTS within Europe is negligible.